The Influence of the Osmotic Dehydration Process on Physicochemical Properties of Osmotic Solution - Lech, Krzysztof (Molecules, 2017)
The osmotic dehydration (OD) process consists of the removal of water from a material during which the solids from the osmotic solution are transported to the material by osmosis. This process is commonly performed in sucrose and salt solutions. Taking into account that a relatively high consumption of those substances might have a negative effect on human health, attempts have been made to search for alternatives that can be used for osmotic dehydration. One of these is an application of chokeberry juice with proven beneficial properties to human health. This study aimed to evaluate the physicochemical properties of the OD solution (chokeberry juice concentrate) before and after the osmotic dehydration of carrot and zucchini. The total polyphenolics content, antioxidant capacity (ABTS, FRAP), dynamic viscosity, density, and water activity were examined in relation to the juice concentration used for the osmotic solution before and after the OD process. During the osmotic dehydration process, the concentration of the chokeberry juice decreased. Compounds with lower molecular weight and lower antioxidant capacity present in concentrated chokeberry juice had a stronger influence on the exchange of compounds during the OD process in carrot and zucchini. The water activity of the osmotic solution increased after the osmotic dehydration process. It was concluded that the osmotic solution after the OD process might be successfully re-used as a product with high quality for i.e. juice production.